Internet of Things in Higher Education - Mansirat Kaur, Harleen Kaur, Saranjeet Kaur , Amandeep Singh (International Journal of Advanced Science and Technology, 2020)
In the coming years, technology will leave a great impact on education. Internet Of Things Plays a vital role in education. Most of the institutes take help of IoT to provide smart classes to students and to enhance their learning experience outcomes. With the growing vogue of IoT, the wearable devices are made for students with small sensors to connecting them with learning system. IoT enhances the learning system by providing the small gadgets to the students like:-IPad, electronic white boards, Laptops, Tablets and eBooks by using these gadgets teachers can interact with students. By using these digital transformation devices will reveal new awareness that will change the learning and implement things used in education system.